2021
DOI: 10.1039/d1ra03041h
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-initiated high strength chitosan/lithium sulfonate double network hydrogel/aerogel with porosity and stability for efficient CO2 capture

Abstract: Chitosan hydrogel is regenerated from alkali/urea aqueous solution and the lithium sulfonate second network is introduced by electron beam radiation-initiated in situ free radical polymerization. The freeze-dried aerogel has CO2 capture capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…Based on a previous research, the CO 2 uptake values of the amine-functionalized mesoporous hybrid materials prepared by Velikova et al could reach about 0.69 mmol/g at 100 kPa and 273 K. In addition, many other aerogels were studied as CO 2 capture materials, such as PI aerogels (1.26 mmol/g at 100 kPa and 298 K), 12 BN aerogels (0.68 mmol/g at 100 kPa and 298 K), 54 GO-based aerogel (1.18 mmol/g at 100 kPa and 298 K), 6 and chitosan/lithium sulfonate double network aerogel (1.39 mmol/g at 100 kPa and 298 K). 55 Therefore, a CO 2 capture value of 5.89 mmol/g at 100 kPa and 298 K in this study is substantially higher than the values of the other aerogels reported under the similar conditions and comparable to those of amine hybrid aerogel (6.66 mmol/g at 303 K). 51 OIHA-3 retains a CO 2 adsorption capacity of 5.45 mmol/g after six cycles, which is 92.69% of the initial value, demonstrating its excellent cyclic adsorption performance (Figure 4e).…”
Section: Acs Applied Nano Materialscontrasting
confidence: 44%
See 1 more Smart Citation
“…Based on a previous research, the CO 2 uptake values of the amine-functionalized mesoporous hybrid materials prepared by Velikova et al could reach about 0.69 mmol/g at 100 kPa and 273 K. In addition, many other aerogels were studied as CO 2 capture materials, such as PI aerogels (1.26 mmol/g at 100 kPa and 298 K), 12 BN aerogels (0.68 mmol/g at 100 kPa and 298 K), 54 GO-based aerogel (1.18 mmol/g at 100 kPa and 298 K), 6 and chitosan/lithium sulfonate double network aerogel (1.39 mmol/g at 100 kPa and 298 K). 55 Therefore, a CO 2 capture value of 5.89 mmol/g at 100 kPa and 298 K in this study is substantially higher than the values of the other aerogels reported under the similar conditions and comparable to those of amine hybrid aerogel (6.66 mmol/g at 303 K). 51 OIHA-3 retains a CO 2 adsorption capacity of 5.45 mmol/g after six cycles, which is 92.69% of the initial value, demonstrating its excellent cyclic adsorption performance (Figure 4e).…”
Section: Acs Applied Nano Materialscontrasting
confidence: 44%
“…However, excessive temperature could make the motion of CO 2 molecules too fast to be stably captured by amine groups and micropores, and this would lead to a decrease in the uptake volume. Based on a previous research, the CO 2 uptake values of the amine-functionalized mesoporous hybrid materials prepared by Velikova et al could reach about 0.69 mmol/g at 100 kPa and 273 K. In addition, many other aerogels were studied as CO 2 capture materials, such as PI aerogels (1.26 mmol/g at 100 kPa and 298 K), BN aerogels (0.68 mmol/g at 100 kPa and 298 K), GO-based aerogel (1.18 mmol/g at 100 kPa and 298 K), and chitosan/lithium sulfonate double network aerogel (1.39 mmol/g at 100 kPa and 298 K) . Therefore, a CO 2 capture value of 5.89 mmol/g at 100 kPa and 298 K in this study is substantially higher than the values of the other aerogels reported under the similar conditions and comparable to those of amine hybrid aerogel (6.66 mmol/g at 303 K) .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in 2021, Liu and colleagues developed a model high-strength hydrogel and aerogel using CS and lithium sulfonate double networks using an electron beam. 178 The aerogels had a double network structure with CO 2 -philic properties, which gave them a porous structure and 67.9 mg g −1 CO 2 capture capacity at 0.1 MPa and 298 K, indicating that they had a HSSA of 114.18 m 2 g −1 . Applications for harvesting CO 2 in real-world settings are feasible because of the physical and chemical strength of the aerogel.…”
Section: Mechanism For Co 2 Capturementioning
confidence: 97%
“…The resulting aerogels display excellent physical and chemical stability with a porous structure ideal for CO 2 capture. This cost-effective approach demonstrates promising applications in the development of CO 2 solid adsorbents (as shown in Figure 8 b) [ 101 ].…”
Section: Brief Application Of Hydrogelsmentioning
confidence: 99%